2018 44th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2018
DOI: 10.1109/seaa.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Study on Source Code Reviewer Recommendation

Abstract: Context: Software code reviews are an important part of the development process, leading to better software quality and reduced overall costs. However, finding appropriate code reviewers is a complex and time-consuming task. Goals: In this paper, we propose a large-scale study to compare performance of two main source code reviewer recommendation algorithms (RevFinder and a Naïve Bayes-based approach) in identifying the best code reviewers for opened pull requests. Method: We mined data from Github and Gerrit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…We also searched for publicly available datasets for further comparison. Lipcak and Rossi [12] review different approaches on code reviewer recommendation and create a dataset publicly available [12] Naive-Bayes --Code RevFinder [22] File path similarity + -Code Correct [18] Developer experience -+ Code RevRec [26] Hybrid of information retrieval and file location --Code Jeong et al [6] Bayesian network -+ Code cHRev [29] Expertise model --Code Developer-Source code graph [11] Random walk algorithm --Code TIE [24] Text and File Location Analyses --Code CoreDevRec [7] Support vector machine --Code RSTrace Know-about metric + + Any for comparison with other approaches. The dataset includes code review information about 51 projects (37 from GitHub and 14 from Gerrit) and it is available on GitHub.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also searched for publicly available datasets for further comparison. Lipcak and Rossi [12] review different approaches on code reviewer recommendation and create a dataset publicly available [12] Naive-Bayes --Code RevFinder [22] File path similarity + -Code Correct [18] Developer experience -+ Code RevRec [26] Hybrid of information retrieval and file location --Code Jeong et al [6] Bayesian network -+ Code cHRev [29] Expertise model --Code Developer-Source code graph [11] Random walk algorithm --Code TIE [24] Text and File Location Analyses --Code CoreDevRec [7] Support vector machine --Code RSTrace Know-about metric + + Any for comparison with other approaches. The dataset includes code review information about 51 projects (37 from GitHub and 14 from Gerrit) and it is available on GitHub.…”
Section: Resultsmentioning
confidence: 99%
“…In this subsection, results from these approaches will be discussed and compared with RSTrace. We implemented the Naive-Bayes algorithm that is described by Lipcak and Rossi [12]. The results of the comparison between RSTrace and Naive-Bayes is shown in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yu et al (2014) proposed a reviewer recommendation algorithm based on the review network. Lipcak et al (2018) conducted big data experiments on various methods above and found that the results of these methods for large-scale projects are not very satisfactory, but they have a good effect on medium-scale projects. Xia et al (2017) proposed a recommendation algorithm that considers implicit relations and neighborhood models.…”
Section: Reviewer Recommendationmentioning
confidence: 99%